Pendeteksian Multi Objek Menggunakan Template Matching - Arlin Purnomo (CV. Multi Kreasi Media, 2023)
Object is a conceptual form or object that exists in our environment, object tracking aims to detect and follow the position of a desired moving object, object tracking is needed by various kinds of vision based applications such as human computer interfaces, video compression/communication and security systems. Template matching is a method used to measure the similarity of an image with a template image, by searching for certain features of both. The similarity of two images can be calculated by calculating the correlation value. The researcher identified that the problems faced were: there was no research that applied a method to detect multi-object objects. The purpose of this study is to apply the template matching method to detect multi-object objects, namely character objects, faces and objects in the form of animals. The results of this study prove that template matching can detect multi-object objects.